Budget Institutions and Macro-Fiscal Forecast Errors in Sub-Saharan Africa: Indicator-Level Analysis - Alade, Adekunle Sarafa; Kilishi, Abdulhakeem Abdullahi (Journal of Developing Economies, 2024)
The annual fiscal budget of any economy gives projections about key economic indicators. Forecasts of these key variables are often at variance with actual realisations at the end of the fiscal year, thereby inducing animal spirits in Sub-Saharan Africa. Past studies focused on the roles of budget institutions and considered only two indicators of budget institutions- centralization and rules and control, thereby ignoring other indicators- transparency, comprehensiveness, and credibility and sustainability indices. This study therefore investigated the roles of budget institutions on macro-fiscal forecast errors, using all existing indicators of budget institutions in SSA. This study was based on rational expectations theory. Empirical models were formulated for growth, inflation, and fiscal balance forecast errors. A panel of data that spanned 2006 to 2021 for 43 countries was gathered. Forecast values were estimated from country’s annual budget speeches, World Development Indicators and Fiscal Space Database. Indices of various indicators of budget institutions were constructed using information from the Collaborative African Budget Reforms Initiative (CABRI), Open Budget Index of the International Business Partnership (IBP) and Public Expenditure and Financial Analysis (PEFA). The models were estimated using GMM System) estimation technique. Estimated results show that only budget procedural rules and credibility and sustainability indices have significant and negative effect on fiscal balance forecast error. No evidence was found that growth and inflation forecast errors were influenced by budget institutions. The implication of this finding is that fiscal budgets based on established procedures and with some level of credibility and sustainability matter for reducing fiscal balance forecast error.